N-Heterocyclic carbene catalyzed chemo- and enantioselective cross-benzoin reaction of aldehydes with isatins. Issue 2 (28th November 2018) - Xu, Jianfeng; Peng, Jingyi; He, Chonglong; Ren, Hongjun
Abstract : A highly chemoselective N-heterocyclic carbene catalyzed intermolecular cross-benzoin reaction of aldehydes with isatins to afford enantioenriched 3-substituted-3-hydroxyoxindoles is described. Abstract : A highly chemoselective intermolecular cross-benzoin reaction of aldehydes with isatins enabled by asymmetric N-heterocyclic carbene (NHC) catalysis is described, and it provides 3-substituted-3-hydroxyoxindoles in moderate to good yields with moderate to excellent enantioselectivities. This reaction can be readily scaled up, the products could be straightforwardly reduced to the corresponding 1, 2-diols, and the trityl (Trt) protecting group could be easily removed without erosion of enantioselectivities.